Update on plague in Peru - Maguiña Vargas, Ciro (2015)
Four cases of pneumonic plague appeared for the first time in Peru in July 2010 in the coast of La Libertad department. This is a serious event for Peruvian public health and reveals that there are ancestral infectious diseases in our country that require inversion and support. Consequently we will do a short review on this historical ailment in Peruvian medicine.